Biomonitoring in the Caucasus Biodiversity Hotspot: The ecological and habitat preferences of Epeorus (Caucasiron) znojkoi (Ephemeroptera, Heptageniidae) from Northeastern Turkey - Gencer Türkmen (Kuwait Journal of Science)
The present study aimed to clarify the ecological and habitat preferences of Epeorus (Caucasiron) znojkoi (Tshernova, 1938) in the Turkish part of the Caucasus Biodiversity Hotspot, and to discuss its usefulness in biomonitoring and water quality assessment. Despite being a common species in the Caucasus, there are no detailed studies have occurred on the ecological demands of this species. Epeorus (C.) znojkoi specimens were collected from 20 sites located in Northeastern Turkey, and seven habitat characteristics were determined. In addition, nine physicochemical variables were measured and analyzed at each site. Pearson Correlation Analysis and ANOVA were used to define the relationship between the variables and the abundance of E (C.) znojkoi. The results showed E (C.) znojkoi to be a rheophilic and psychrophilic species preferring the epirhithron of oligosaprobic and β-mesosaprobic streams with stony substrate. The stream sections with a high abundance of E (C.) znojkoi correspond to I. Class water quality with regard to all physicochemical variables (except PO4–P). The correlation analysis between physicochemical variables and the abundance of E (C.) znojkoi revealed the presence of a strong negative relationship to water temperature, electrical conductivity, and SO4; and a positive relationship to NO4–N. In summary, E (C.) znojkoi can be considered a useful indicator species of high-water quality for the streams within the investigated area.